Reflections of AB-English Students on Their English Language Experiences (Asia Pacific Journal of Social and Behavioral Sciences, 2015)
This study seeks to investigate the language learning experiences of the thirty-nine AB-English majors of Bukidnon State University who were selected through fish-bowl technique from the 157 students enrolled in the AB-English program. Analyses done on the diary, questionnaire, and unstructured interview revealed that the motivation, learner's belief, self-monitoring, language anxiety, activities, and strategies were the prevailing factors that influenced the learning of English of the participants.
Keywords: Diary, English language learning experiences, reflections, learner’s belief, anxiety, self-motivated learner, teacher’s role